To determine which example correctly demonstrates polynomial addition, let's perform the addition for the expression \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) \).
-
Combine the \( x^2 \) terms:
- \( 2x^2 + 3x^2 = 5x^2 \)
-
Combine the \( x \) terms:
- \( 6x + 3x = 9x \)
-
Combine the constant terms:
- \( 1 + 9 = 10 \)
Putting it all together, we have: \[ (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 \]
Now we can review the provided options:
- \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 \) - Correct
- \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^4 + 9x^2 + 10 \) - Incorrect
- \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = -x^2 + 3x - 8 \) - Incorrect
- \( (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 13x^2 + 9x + 10 \) - Incorrect
The correct response is: (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10.